Community Participation in Sustainable Development Goals: Experiences in West Java, Indonesia - Moh Dulkiah; Marlan Marlan; Rudi Kresna; Sarbini Sarbini; Asep Dadan Wildan (UIN Sunan Gunung Djati, 2025)
This research examines community participation in sustainable development in West Java, Central Java, and East Java Provinces, Indonesia, which aims to integrate sustainable development goals into policies and activities at the village level. Although the Sustainable Development Goals (SDGs) program has been implemented, citizen participation remains minimal. The research method uses a qualitative approach with data collection techniques through field research, participatory observation, literature research, and in-depth interviews with community leaders and relevant stakeholders. The main findings show that community groups play an active role in physical development and enhance local capacity in resource management, with significant support for the sustainability of SDG programs at the village level. The complexity of economic, social, and cultural factors has influenced their participation, as well as its implications for achieving sustainable development goals. This research contributes to a deeper understanding of the role of community societies in the context of village development, with implications for the development of more inclusive and sustainable policies in the future.